Crystal structure and Hirshfeld surface analysis of 3-(bromomethyl)-2-[1,2-dibromo-2-(6-nitrobenzo[d][1,3]dioxol-5-yl)ethyl]-1-(phenylsulfonyl)-1H-indole chloroform 0.585-solvate - Nagaraj Achyuta; Somarathinam Kanagasabai; Pavunkumar Vinayagam; Arasambattu K. Mohanakrishnan; Namasivayam Gautham; Krishnasamy Gunasekaran (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The title indole derivative, C24H17Br3N2O6S, crystallizes with a partial occupancy [0.585 (4)] CHCl3 solvent molecule. The dihedral angles between the indole ring system and pendant nitrobenzodioxolane rings system and phenylsulfonyl ring are 4.81 (14) and 72.24 (19)°, respectively. In the crystal, the indole molecules are linked to each other and to the chloroform molecule by weak C—H...O, C—H...Cl, C—H...π, C—Br...π and C—Cl...π and aromatic π–π stacking interactions. A Hirshfeld surface analysis was carried out and the intermolecular contacts with the most significant contributions are H...O/O...H (24.3%), H...H (18.4%), Br...H/H...Br (16.8%) and C...H/H...C (8.4%).